EFEKTIVITAS PEMBELAJARAN MENGIDENTIFIKASI UNSUR-UNSUR TEKS BERITA MENGGUNAKAN METODE EARTH DAN PQRST PADA SISWA DI SMP ANGKASA LANUD SOEWONDO - Nova Triana Tarigan; Rizki Bastanta B Manalu; Yana Br Sembiring (JURNAL CURERE, 2022)
Reading skills are skills that are the basis when someone will do something. Reading skill is one of the skills used to get information. Reading skill is a process in which it contains certain steps so as to achieve an understanding of a reading. The results of observations in several schools, the basic competence of identifying less than optimally learned. Learning to identify is learning that introduces, seeks, examines information contained in a text. However, at the time of learning, educators did not explain how the process or how to identify, educators only relied on textbooks or textbooks, so that the identification material was not accepted by students. In addition, students are also less directed in reading and looking for information in the text. The purpose of this study is to describe the effectiveness of learning to identify news text elements with the EARTH method, to describe the effectiveness of learning to identify news text elements using the PQRST method for students VIII and IX at SMP Angkasa Lanud Soewondo. The research design used in this study is a quasi-experimental design in the form of a nonequivalent control group design. The sample in this study were students of class VIII and IX at SMP Angkasa Lanud Soewondo in North Sumatra Province. The research data are in the form of trial values before being given treatment (pretest) and test values after being given treatment (posttest) in the sample class. The number of samples used in this study were 62 students at SMP Angkasa Lanud Soewondo. The results showed that the results of calculations using the t-test also proved that the PQRST method was effectively used with the acquisition of sig.(2tailed) = 0.000 or sig. <0.05 so Ha is accepted which means that the PQRST method is more effective in learning to identify news text elements than learning to identify news text elements using the EARTH method.